The Existence in a Black Skin: contributions of Fanon for the Existential Psychology (Phenomenology, Humanities and Sciences, 2022)
This text discusses the issue of ontological difference, according to the perspective of decolonial thinkers and its importance for Existence Psychology. At first, the article argues that Existential Psychology should pay attention to the ontology of the colonized, since the philosophical bases on which it is based are primarily European and disregard the specifici-ties of the post-colonial experience from the point of view of the colonized. This experience was described by the Martinican psychiatrist Franz Fanon, whose work can support the cons-truction of an anti-racist Existential Psychology. It is understood that racism is constitutive of modernity-coloniality being contained in European ontologies from the modern, such as Descartes, to the contemporary as proposed by Heidegger. Fanon provides an unveiling of this structural racism in modern philosophy, by highlighting the experience of colonized blacks, which, according to the authors of the decolonial movement like Dussel, Maldonado-Torres and Alberto Quijano, contributed to the consolidation of this movement. The text concludes by emphasizing the importance of a plural Psychology and paying attention to the diversity of experiences.
Keywords: Decolonial Thought; Existential Psychology; Racism; Ontology